Adding functional properties to beer with jasmine tea extract - Chen, De-Quan; Zou, Chun; Huang, Yi-Bin; Zhu, Xuan; Contursi, Patrizia; Yin, Jun-Feng; Xu, Yong-Quan (Frontiers in Nutrition, 2023)
Hops provide the characteristic bitter taste and attractive aroma to beer; in this study, hops were replaced by jasmine tea extract (JTE) during late-hopping. The addition of JTE improved the beer foam stability 1.52-fold, and increased the polyphenol and organic acid contents. Linalool was the most important aroma compound in hopped (HOPB) and jasmine tea beer (JTB), but other flavor components were markedly different, including dimeric catechins, flavone/flavonol glycosides, and bitter acids and derivatives. Sensory evaluation indicated that addition of JTE increased the floral and fresh-scent aromas, reduced bitterness and improved the organoleptic quality of the beer. The antioxidant capacity of JTB was much higher than that of HOPB. The inhibition of amylase activity by JTB was 30.5% higher than that of HOPB. Functional properties to beer were added by substituting jasmine tea extract for hops during late hopping.